Simulation Study of Flange Characteristic at Various Operating Condition - Ismail, Amirul Iezlan; Mustaffa, Norrizal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Flanges are integral components in piping systems, their advantages in terms of easy maintenance and installation, however, come with challenges, particularly in their ability to withstand pressure and ensure durability. This study focuses on investigating the durability of DIN 2633 PN16 Weld Neck Raised Flanges (WNRF) under various operating conditions. The problem statement of this study was to determine the breaking points in connectors especially under higher pressure. Besides that, it is also difficult to determine suitable dimensions for operational needs. Lastly, the problem statement was flange failure risks may lead to accidents and productivity loss. Objectives of this study are to compare flange durability under specific operating conditions and to evaluate the ability of DIN 2633 PN16 flanges to withstand pressures beyond the nominal pressure of 16 bar. This study employs SolidWorks Software for comprehensive simulation testing to evaluate the performance and durability of DIN 2633 PN16 Weld Neck Raised Flanges (WNRF). The research focuses on the coupling of weld neck raised flanges, examining three different types with 4-point, 8-point, and 12-point bolts under varying pressures of 16, 18, and 20 bar. Steam serves as the working fluid, and the study emphasizes the influence of flange diameter (DN) on the results. The materials used for the flanges were cast carbon steel, and the applied torque for bolt tightening was determined according to the specified table. This study methodology was utilizing SolidWorks Software to investigate the structural performance of DIN 2633 PN16 Weld Neck Raised Flanges (WNRF). The first step involves the design of 3D flanges within the SolidWorks environment. Then, a static simulation was conducted to evaluate various aspects, including stress distribution, displacement analysis, strain evaluation, and factor of safety assessment. Based on the results obtained, this study acknowledges in respects for safety uses beyond 16 bar of pressure for flanges dimension DN200 while for DN65 and DN80 seems to shows results as expected which was safe to use beyond 16 bar of pressure.